Structure-guided discovery of novel AflG inhibitors for aflatoxin contamination control in aspergillus flavus - Wang, Fenghua; Zhou, Weijie; Yang, Maohua; Niu, Jinlu; Huang, Wenjie; Chen, Zhaofu; Chen, Yuanyuan; Wang, Dongdong; Zhang, Jun; Wu, Shaowen; Yan, Shijuan (Frontiers in Microbiology, 2024)
Aflatoxins (AFs) are highly carcinogenic metabolites produced by Aspergillus species that can contaminate critical food staples, leading to significant health and economic risks. The cytochrome P450 monooxygenase AflG catalyzes an early step in AF biosynthesis, resulting in the conversion of averantin (AVN) to 5'-hydroxy-averantin. However, the molecular mechanism underlying the AflG-AVN interaction remains unclear. Here, we sought to understand the structural features of AflG in complex with AVN to enable the identification of inhibitors targeting the AflG binding pocket. To achieve this goal, we employed a comprehensive approach combining computational and experimental methods. Structural modeling and microsecond-scale molecular dynamics (MD) simulations yielded new insights into AflG architecture and unveiled unique ligand binding conformations of the AflG-AVN complex. High-throughput virtual screening of more than 1.3 million compounds pinpointed specific subsets with favorable predicted docking scores. The resulting compounds were ranked based on binding free energy calculations and evaluated with MD simulations and in vitro experiments with Aspergillus flavus. Our results revealed two compounds significantly inhibited AF biosynthesis. Comprehensive structural analysis elucidated the binding sites of competitive inhibitors and demonstrated their regulation of AflG dynamics. This structureguided pipeline successfully enabled the identification of novel AflG inhibitors and provided novel molecular insights that will guide future efforts to develop effective therapeutics that prevent AF contamination.